Technological aspects of delivering cryotherapy for prostate cancer. (March 2014) - Lau, Benjamin; Shah, Taimur Tariq; Valerio, Massimo; Hamid, Sami; Ahmed, Hashim Uddin; Arya, Manit
Abstract : Since the era of prostate specific antigen (PSA) testing, there has been a stage and grade migration seen with prostate cancer along with a reduction in mortality. Subsequently, concerns have been raised about the over treatment of patients following the diagnosis of localized prostate cancers. Cryotherapy, in which extremely low temperatures induce cell death via multiple mechanisms, has seen a drastic improvement in its technology since the 1800s. Such advances have improved oncological outcomes while reducing complication rates. Furthermore, technological advances have allowed the development of focal cryotherapy which aims to reduce morbidity associated with more radical whole-gland therapies. There is growing evidence that focal cryotherapy provides good oncological and morbidity rates when compared with traditional radical/whole-gland therapies.